Monomorphic pattern for BMPR1B gene in prolific Alpine x Beetal and Saanen x Beetal goats - Shweta Sahoo; Amritanshu Upadhyay; Rani Alex; S.K. Rathee; G.R. Gowane (Journal of Livestock Biodiversity, 2025)
The present study was aimed to delineate genetic variability of Bone Morphogenetic Protein Receptor type 1B (BMPR1B) or FecB gene in Alpine x Beetal and Saanen x Beetal crossbred goats maintained at ICAR-National Dairy Research Institute, Karnal, Haryana. The mutation present at (Q249R) in BMPR1B gene induces early maturity of ovarian follicles by increasing the sensitivity of the follicles to FSH leading to release of more eggs per cycle which increases fecundity and forms the basis of marker assisted selection. Genomic DNA was extracted from blood samples of 88 animals from both the breeds and one set of primers were used to amplify a 140bp fragment of FecB gene. The amplified fragments were digested using Ava II enzyme. All the animals under study were found to be non-carriers for FecB mutation evidenced by the absence of any polymorphism observed after PCR-RFLP suggesting no apparent association of this mutation with fecundity in Alpine x Beetal and Saanen x Beetal crossbred goats.